The Role of Rhythm in Speech and Language Rehabilitation: The SEP Hypothesis - Fujii, Shinya; Wan, Catherine Y. (Frontiers in Human Neuroscience, 2014)
For thousands of years, humans have engaged in rhythmic activities such as drumming, dancing, and singing. Rhythm can be a powerful medium to stimulate communication and social interactions, due to the strong sensorimotor coupling. For example, the mere presence of an underlying beat or pulse can result in spontaneous motor responses such as hand clapping, foot stepping, and rhythmic vocalizations. Examining the relationship between rhythm and speech is fundamental not only to our understanding of the origins of human communication, but also in the treatment of neurological disorders. In this paper, we explore whether rhythm has therapeutic potential for promoting recovery from speech and language dysfunctions. Although clinical studies are limited to date, existing experimental evidence demonstrates rich rhythmic organization in both music and language, as well as overlapping brain networks that are crucial in the design of rehabilitation approaches. Here, we propose the “SEP” hypothesis, which postulates that 1) “Sound Envelope Processing” and 2) “Synchronization and Entrainment to Pulse” may help stimulate brain networks that underlie human communication. Ultimately, we hope that the SEP hypothesis will provide a useful framework for facilitating rhythm-based research in various patient populations.